Taoism in A. R. Ammons Book of Poems A Coast of Trees (Journal of the College of Basic Education, 2022)
A Coast of Trees (1981) is a book comprising combination of 37 poems. The research paper provides explanation of the poems in the light of Taoistic views. A.R. Ammons (1926-2001) closely follow the Taoistic views in the book. This book clearly reveals many features of the nature that involves dynamic changes and evolution of different animals and objects. In first series of poems, Ammons describes the true picture of universe through keen observations. Taoism provides insight into humans and things that interact with each other in real time. Negating the western perspective of seeing things, the oriental school of thought prevails.Taoism is closer in vision to Buddhism due to a number of reasons. Firstly, they focus more on the soul than the physical existence. Secondly, after life and incarnation are common to both beliefs. Thirdly, meditation and righteous life are commonly held beliefs in these religions. Most importantly, the explanation of happenings in nature in terms of dynamic models is also similar. Most of the poems show supremacy of nature and reality of death through different creatures and physical objects. Poems that point out the paradox of things like life and death, reality and appearance show larger themes of the strong integration between man and nature. The poet points out that Nature itself is constructive in its dynamic evolution unless man intervenes to break its cycle. If he follows nature’s path, he will not face any sense of loneliness and loss, as his poems show.